Bacillus velezensis CNPMS-22 as biocontrol agent of pathogenic fungi and plant growth promoter - Figueiredo, José Edson Fontes; Diniz, Gisele de Fátima Dias; Marins, Mikaely Sousa; Silva, Felipe Campos; Ribeiro, Vitória Palhares; Lanza, Fabrício Eustáquio; Oliveira-Paiva, Christiane Abreu de; Cruz-Magalhães, Valter (Frontiers in Microbiology, 2025)
IntroductionBacillus velezensis is a ubiquitous bacterium with potent antifungal activity and a plant growth promoter. This study investigated the potential of B. velezensis CNPMS-22 as a biocontrol agent against phytopathogenic fungi under diverse experimental conditions and its potential as a plant growth promoter. Genome sequencing and analysis revealed putative genes involved in these traits.MethodsThis research performed in vitro experiments to evaluate the CNPMS-22 antagonistic activity against 10 phytopathogenic fungi using dual culture in plate (DCP) and inverted sealed plate assay (ISP). Greenhouse and field tests evaluated the ability of CNPMS-22 to control Fusarium verticillioides in maize plants in vivo. The CNPMS-22 genome was sequenced using the Illumina HiSeq 4,000 platform, and genomic analysis also included manual procedures to identify genes of interest accurately.ResultsCNPMS-22 showed antifungal activity in vitro against all fungi tested, with notable reductions in mycelial growth in both DCP and ISP experiments. In the ISP, volatile organic compounds (VOCs) produced by CNPMS-22 also altered the mycelium coloration of some fungi. Scanning electron microscopy revealed morphological alterations in the hyphae of F. verticillioides in contact with CNPMS-22, including twisted, wrinkled, and ruptured hyphae. Eight cluster candidates for synthesizing non-ribosomal lipopeptides and ribosomal genes for extracellular lytic enzymes, biofilm, VOCs, and other secondary metabolites with antifungal activity and plant growth promoters were identified by genomic analysis. The greenhouse and field experiments showed that seed treatment with CNPMS-22 reduced Fusarium symptoms in plants and increased maize productivity.ConclusionOur findings highlight the CNPMS-22’s potential as bioinoculant for fungal disease control and plant growth with valuable implications for a sustainable crop productivity.